Biogenic synthesis: a sustainable approach for nanoparticles synthesis mediated by fungi. Issue 5 (4th May 2023) - Chauhan, Anuj; Anand, Jigisha; Parkash, Vipin; Rai, Nishant
Abstract: Biogenic synthesis of nanoparticles (NPs) is emerging as a feasible, economical, sustainable, biocompatible, and alternative approach to utilize biomolecules derived from the organisms. The use of microbes or their metabolites for biogenic NPs synthesis also imparts the biological active antimicrobial potential of the organism which has widened the application of NPs in an effective and economically friendly way. The biological reduction of metals provides NPs of desirable size and morphology with higher physiochemical characteristics, lower toxicity, and high stability. Fungi are the most preferred for the biogenic synthesis of NPs due to high biomass production, secretion of a high quantity of extracellular nano-particles stabilizing proteins, ease in handling, and high metal tolerance. The present review provides an overview of the biogenic synthesis of metal NPs using micro and macrofungi, mechanism, their optimization process and their applications in the field of agriculture.